2000
DOI: 10.1016/s1369-703x(99)00047-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of dextransucrase, dextran and fructose from sucrose using Leuconostoc mesenteroides NRRL B512(f)

Abstract: The production of dextransucrase, dextran and fructose by sucrose fermentation using Leuconostoc mesenteroides NRRL-B512(F) was studied in batch operation in a bioreactor with total working volume of 1.5 dm 3 . The effect of temperature (20 to 40 • C), pH (5.5 and 6.7) and sucrose concentration (10 to 120 g/l) on process performance was studied. The optimum conditions for dextran and fructose production were T = 35 • C and pH = 5.5.Cell growth is not inhibited by high sucrose concentrations; however, for sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 19 publications
4
53
0
3
Order By: Relevance
“…On comparison of dextran and sucrose concentration profiles in the bioreactor, it was found that the dextran concentration peaked after the commencement of sucrose consumption. In bioreactor, the enzyme activity (10.9 U/ml) and the cell optical density both, reached maximum at 14h, which is in agreement with the report of growth associated biosynthesis of dextransucrase (Santos et al, 2000;Rodrigues et al, 2003, Michelena et al, 2003. Oxygen is known to have positive effects on the growth of certain strains of L. mesenteroides (Veljkovic et al 1992).…”
Section: Optimization Of Medium Composition and Experimental Validatisupporting
confidence: 90%
“…On comparison of dextran and sucrose concentration profiles in the bioreactor, it was found that the dextran concentration peaked after the commencement of sucrose consumption. In bioreactor, the enzyme activity (10.9 U/ml) and the cell optical density both, reached maximum at 14h, which is in agreement with the report of growth associated biosynthesis of dextransucrase (Santos et al, 2000;Rodrigues et al, 2003, Michelena et al, 2003. Oxygen is known to have positive effects on the growth of certain strains of L. mesenteroides (Veljkovic et al 1992).…”
Section: Optimization Of Medium Composition and Experimental Validatisupporting
confidence: 90%
“…The most extensively studied dextransucrase from the commercially important strains NRRL B-512 and B-512F of L. mesenteroides synthesizes a soluble linear ␣-1,6-linked dextran with about 5% randomly distributed ␣-1,3-branched linkages of up to 50 to 100 residues (168,176,191). The long branches are important factors for properties of the dextran (209).…”
Section: Structure and Properties Of Dextranmentioning
confidence: 99%
“…Mesenteroides y Leuconostoc mesenteroides subsp. Dextranicum producen dextranas en rendimientos elevados, usando la enzima extracelular dextrana-sacarasa durante el metabolismo de la sacarosa [73,92].…”
Section: Exopolisacáridos -Eps -unclassified
“…Los lactobacilos son comúnmente empleados como starters en la manufacturación de productos lácteos, siendo el caso del Lactobacillus rhamnosus ssp que es una especie productora de EPS con potencial probiótico [25,63,12]. Otras especies con potencial de producción de EPS son los Lactococcus lactis spp [113,12,36]; Leuconostoc spp., Leuconostoc fructosum, Leuconostoc mesenteroides spp [6,92,42,12]; Pediococcus acidilactici var [100] y Proponibacterium como Propionibacterium freudenreichii spp [47,75,107,35,60], los cuales son de interés por sus efectos estimulantes sobre probióticos y por ser, también, productores de vitamina B12 [107].…”
Section: Exopolisacáridos -Eps -unclassified